Estimation of inter-individual variability of protein requirement by indicator amino acid oxidation method - Aoki, Yuma; Nakano, Makoto; Hayamizu, Kohsuke; Izumo, Nobuo (Journal of Clinical Biochemistry and Nutrition, 2021)
The indicator amino acid oxidation (IAAO) method is a recently developed method to determine the protein requirement and is particularly useful for analyzing human subjects because of its minimal invasiveness. IAAO study is performed using two-phase regression analysis, with the break-point between these phases being the estimated average requirement. However, this method requires that the break-point lie within a certain range in advance, which is in practice difficult. Recently, the change-point regression model (CPRM) has been proposed to be more effective for two-phase regression analysis. There is also a need to re-evaluate the value corresponding to the recommended dietary allowance. Calculation of the recommended dietary allowance requires data on the average requirement and the inter-individual variability of this requirement. However, no inter-individual variability values have been reported in the IAAO method. The aim of this study was thus to estimate the inter-individual variation in protein requirement using CPRM. From seven IAAO studies, the inter-individual variability was estimated as a coefficient of variation of about 20%. The coefficient of variation of the protein requirement determined by IAAO study was wider than the ordinary coefficient of variation obtained from the nitrogen balance test.